Antecedents of need fulfillment among elite athletes and coaches: A qualitative approach - Frøyen, A. F.; Pensgaard, A. M. (International Journal of Applied Sports Sciences, 2014)
The main objective of study 1 and 2 was to provide, within the framework of basic psychological need theory (BPNT), a mini-theory in self-determination theory (SDT), more in-depth understanding of the needs which athletes and coaches have in relation to each other. In particular, we wanted to investigate antecedents of the three basic psychological needs of athletes and coaches who compete at the elite level in sport. The two studies were conducted with the use of semi-structured interviews. Six former Norwegian world-class athletes participated in study 1 and four coaches with extensive experience within elite sport participated in study 2. In study 1, being seen as a whole person and being recognized in the planning process and the execution of athletes' training emerged as antecedents of autonomy. Help to improve skills and feeling supported as an athlete emerged as important for need satisfaction of competence and relatedness. Potential antecedents of need thwarting were also illuminated. In study 2, feedback on the quality of the coaches' work emerged as an antecedents of need satisfaction of competence. The need to know their athletes` life situation and how they would think and feel in different competitive situations emerged as antecedents of the coaches` need satisfaction of relatedness as it provided them with a sense of security. The results did not reveal any antecedents of need fulfillment of autonomy among the coaches. It was, however, revealed that athletes have the potential to thwart coaches` needs.